2017
DOI: 10.1001/journalofethics.2017.19.12.ecas3-1712
|View full text |Cite
|
Sign up to set email alerts
|

How Should Clinicians Weigh the Benefits and Harms of Discussing Politicized Topics that Influence Their Individual Patients’ Health?

Abstract: Health implications of politically charged phenomena are particularly difficult for physicians to discuss with their patients and communities. Addressing climate change and its associated health effects involves trade-offs between health and economic prosperity, necessitating that physicians weigh the potential benefits and risks of discussing climate change health effects. We argue that the potential benefits of physician communication and advocacy ultimately outweigh the potential risks. Therefore, physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…A trustful physician-patient relationship is central to elicit patients’ perspectives, appreciate their psychosocial context and reach a shared understanding of a problem. Contrary to the apprehension of some physicians [ 8 , 12 ], our findings add weight to the notion that CSHC does not endanger an excellent therapeutic relationship but can potentially strengthen it [ 24 ], particularly if patients and physicians share similar attitudes towards climate change. Previous literature has found that personal connection and continuity of care, as given in general practice, can serve as a prerequisite to talk about more sensitive topics and behaviour change [ 21 ].…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…A trustful physician-patient relationship is central to elicit patients’ perspectives, appreciate their psychosocial context and reach a shared understanding of a problem. Contrary to the apprehension of some physicians [ 8 , 12 ], our findings add weight to the notion that CSHC does not endanger an excellent therapeutic relationship but can potentially strengthen it [ 24 ], particularly if patients and physicians share similar attitudes towards climate change. Previous literature has found that personal connection and continuity of care, as given in general practice, can serve as a prerequisite to talk about more sensitive topics and behaviour change [ 21 ].…”
Section: Discussionsupporting
confidence: 41%
“…Alame et al. even argue that the responsibility of physicians within climate change communication needs to be limited to health concerns [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed associations between political self-positioning, CC attitudes and CSHC preference. As CSHC should be delivered in a patient-centred manner and consider the (environmental) values of patients [ 25 , 67 ], our findings underscore the need for physicians not to provide CSHC uniformly to all patients but to tailor it to patients’ values and needs. To do so, it can be helpful to know patients’ CC-related attitudes or to explore these attitudes.…”
Section: Discussionmentioning
confidence: 91%
“…As an example, veterinarians are more trusted than physicians and viewed positively by the public ( 46 ), which can be beneficial in being part of these important topics. There are guides for other health professions on having conversations about politicized topics which have major impacts on patient health ( 47 ). Human health professionals have already emphasized the need to teach patients about the relevance of climate change to direct patient care ( 48 ).…”
Section: How Can Veterinarians Be Valuable Assets For Climate Change ...mentioning
confidence: 99%